Cutaneous horns: clues to invasive squamous cell carcinoma being present in the horn base - John Pyne (Mattioli1885, 2013)
Background: Cutaneous horns usually develop on a keratinocytic base with the histopathology on a spectrum ranging from benign keratosis through to invasive squamous cell carcinoma (SCC). Some features of horns are easily identified using dermatoscopy.